Ultrasound guided therapeutic injections of the cervical spine and brachial plexus. Issue 1 (February 2014) - Cormick, Wes
Abstract: Introduction : Recent applications in ultrasound imaging include ultrasound assessment and ultrasound guided therapeutic injections of the spine and brachial plexus. Discussion : Ultrasound is an ideal modality for these regions as it allows accurate safe and quick injection of single or multiple sites. It has the added advantages of lack of ionising radiation, and can be done without requiring large expensive radiology equipment. Conclusion : Brachial plexus pathology may be present in patients presenting for shoulder symptoms where very little is found at imaging the shoulder. It is important to understand the anatomy and normal variants that may exist to be able to recognise when pathology is present. When pathology is demonstrated it is easy to do a trial of therapy with ultrasound guided injection of steroid around the nerve lesion. This review will outline the normal anatomy and variants and common pathology, which can be amenable to ultrasound guided injection of steroid.